2018
DOI: 10.1073/pnas.1802345115
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of surface exposed water ice in the lunar polar regions

Abstract: SignificanceWe found direct and definitive evidence for surface-exposed water ice in the lunar polar regions. The abundance and distribution of ice on the Moon are distinct from those on other airless bodies in the inner solar system such as Mercury and Ceres, which may be associated with the unique formation and evolution process of our Moon. These ice deposits might be utilized as an in situ resource in future exploration of the Moon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
248
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(259 citation statements)
references
References 33 publications
7
248
2
2
Order By: Relevance
“…Adapting an intimate mixing model (linearized by mixing single scattering albedos) and considering the effect of porosity on near-infrared reflectance (assuming a porosity of 70%) would produce a slightly higher water ice content, for example,~6.5% for the LCROSS impact site, generally consistent with the detection value for the ejecta plume from the Cabeus crater floor (5.6 ± 2.9%; Colaprete et al, 2010). Recent M 3 spectroscopic modeling calculations for lunar polar PSRs by Li et al (2018) also revealed a higher water ice abundance from intimate mixing modeling than areal mixing modeling. Our investigation also shows 10.1029/2019EA000567…”
Section: Characterization Of Polar Water Ice Exposures and Depositssupporting
confidence: 64%
See 2 more Smart Citations
“…Adapting an intimate mixing model (linearized by mixing single scattering albedos) and considering the effect of porosity on near-infrared reflectance (assuming a porosity of 70%) would produce a slightly higher water ice content, for example,~6.5% for the LCROSS impact site, generally consistent with the detection value for the ejecta plume from the Cabeus crater floor (5.6 ± 2.9%; Colaprete et al, 2010). Recent M 3 spectroscopic modeling calculations for lunar polar PSRs by Li et al (2018) also revealed a higher water ice abundance from intimate mixing modeling than areal mixing modeling. Our investigation also shows 10.1029/2019EA000567…”
Section: Characterization Of Polar Water Ice Exposures and Depositssupporting
confidence: 64%
“…Adapting an intimate mixing model (linearized by mixing single scattering albedos) and considering the effect of porosity on near‐infrared reflectance (assuming a porosity of 70%) would produce a slightly higher water ice content, for example, ~6.5% for the LCROSS impact site, generally consistent with the detection value for the ejecta plume from the Cabeus crater floor (5.6 ± 2.9%; Colaprete et al, ). Recent M 3 spectroscopic modeling calculations for lunar polar PSRs by Li et al () also revealed a higher water ice abundance from intimate mixing modeling than areal mixing modeling. Our investigation also shows that the north polar region hosts more smaller and LOLA albedo anomalous PSRs than in the south polar area, indicating the distribution of surface water ice exposure is more isolated in north polar region than in the south polar region, consistent with previous studies (e.g., Fisher et al, ; Gladstone et al, ; Li et al, ).…”
Section: Constraints On Surface Water Ice Occurrencementioning
confidence: 93%
See 1 more Smart Citation
“…Consider a more detailed (but nonunique) construction where the ice regions (~30% wt icy regolith) like those reported by Li et al (2018) make up about 1% of the area of a 20-km-radius crater floor. This ice-rich area in the crater is then 1.2 × 10 7 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Earth‐based and orbital radar observations of the lunar poles have shown indications for circular polarization ratio anomalies inside PSRs that could indicate buried ice, but these experiments conclusively show that extensive ice deposits like those seen on Mercury are not present on the Moon (Campbell et al, ; Fa & Cai, ; Neish et al, ; Nozette et al, ; Spudis et al, ; Stacy et al, ; Thomson et al, ). At the surface, evidence of patchy surface water that covers roughly 10% of the total PSR area has been presented by workers using LRO Lunar Orbiter Laser Altimeter reflectance measurements, LRO Lyman Alpha Mapping Project UV spectra, and Chandrayan Moon Mineral Mapper infrared spectra, coupled with temperature data from the LRO Diviner thermal radiometer (e.g., Fisher et al, ; Hayne et al, ; Li et al, ; Milliken & Li, ; Zuber et al, ). A statistical approach by Rubanenko et al () concluded that craters in the south lunar polar region have relatively low depth‐diameter ratios and suggested that the shallowing is caused by buried ice; however, because of the statistical nature of the work, they could not identify individual shallowed candidate carters, and the mystery of why there might be an asymmetric distribution of water by any source between the north and south poles remains a mystery and concern.…”
Section: Introductionmentioning
confidence: 99%